ANALISIS FAKTOR PENDORONG DAN PENARIK MASYARAKAT KAMPUNG ARUI DISTRIK KEPULAUAN MOORA Di KABUPATEN NABIRE - Betsy Vivin Misiro; Maria Arim; Elsa Meliala (Sosio Agri Papua, 2021)
Nabire Regency is one of the Districts of the Papua Province which has sufficient facilities. This is the driving and pulling factor for people in small areas, especially those in Arui Village, Moora islands Districts to urbanize to Nabire City, with the aim of getting more adequate income, continuing education, more adequate health services, and fasilities, to market gaerden or marine products. To see the relationship between urbanization of the Arui Village Community with push and pull factors cross tabulation analysis is used to so that it can be seen that there is a relationship between urbanization, whether permanent or temporary, to the driving factors of minimum wages, land area, and availability of facilities (Health education, economy) and factors that attract drinking wages, population, evailability of fasilities (Education, health, worship, economy) entertainment venues, and lifestyle.